TINJUAN YURIDIS KASUS TINDAK PIDANA PENCURIAN DALAM KELUARGA - Irfan Rizky Hutomo; Urip Giyono; Muh Alfi Ihsanu Amala (Jurnal Jendela Hukum, 2023)
"Juridical Review of the Crime of Theft in the Family" This research is motivated by the various efforts made by the authorities and the community members themselves to eradicate the crime of theft. Law enforcement for the crime of theft in the family is not only the task of law enforcement officials, but also participation from within the family, among other things, this can be minimized by efforts to provide knowledge about the law to the family members themselves. In this study, the authors used descriptive qualitative analysis method, which is a research method based on postpositivism philosophy used to examine natural object conditions (as opposed to experiments) where the researcher is the key instrument of data collection techniques. The offenses referred to in Article 367 paragraph (2) and paragraph (3) of the Criminal Code are relative complaint offenses, namely offenses in which the existence of a complaint is only a requirement so that a perpetrator can be prosecuted.